Carolyn Ellis and Art Bochner: Building Connections in Qualitative Research - Stacy Holman Jones (Forum: Qualitative Social Research, 2004)
Carolyn ELLIS and Art BOCHNER tell the stories of their education, their interests in and commitment to qualitative research as a way to make meaning in and through personal relationships, and their passion for creating a community of narrative and autoethnographic researchers as a complement to—rather than a replacement for—the knowledge generated through more traditional forms of qualitative and quantitative research. URN: urn:nbn:de:0114-fqs0403284